GAMBARAN KOMPOSISI TUBUH ANAK USIA 2 _ 5 TAHUN DAN HUBUNGANNYA DENGAN STATUS EKONOMI DI KOTA SEMARANG - M. Zen Rahfiludin; Wulansari -; Ronny Aruben; Martha IK (Universitas Muhammadiyah Semarang, 2005)
ABSTRACTBackground: Children's body composition can be used to assess their nutrition status. It is consisted of 2 tissues: fattissue andfat-free (muscle) tissue. The circumference of the upper arm, the thickness of fat under the skin, the tricepsand the width of the upper arm muscle are commonly used as the standard for measuring the composition of a bodybecause it is cheap and easy to apply; yet rarely practiced. The nutrition status is influenced by the economic and socialcondition of thefamily such as income andfood expenses. Purpose: to describe the composition of body of children age2-5 years old and to analyze the correlation between family income and the cost spending for food with the compositionof their body. Method: this survey is conducted by using the cross sectional approach. The primary data are:circumference of the upper arm, the thicbtess of fat under the skin, the triceps and the width of the upper arm musclesnd the social economic data based on interviews by using questionnaires. The research population is children age 2-5in the area of Puskesmas Bangetayu. From 1227 children in the area, 609 were taken os samples. Results: there is adifference in the thickness of fat under the skin (p:0.001) and the width of the upper arm muscle (p:0,001) betvveenboys and girls. From the bivariat result, there is a correlation between family income and the cost spending on foodwith the circumference of the upper arm, triceps and the width of the upper aftn muscle. Yet, both of them do not haveany correlation with the thiclmess offat under the skin. circumferenceKeywords: Education, economic status, composition of body, children age 2-5